A combined experimental and theoretical approach to atomic structure and segregation at ceramic interfaces - Pennycook, S; Dickey, E; Nellist, P; Chisholm, M; Yan, Y; Pantelides, S (1999)
In the last few years, the scanning transmission electron microscope has become capable of forming electron probes of atomic dimensions. This makes possible the technique of Z-contrast imaging, a method of forming direct images at atomic resolution with high compositional sensitivity. Atomic column positions can be determined to high accuracy from the image, and columns containing high-Z impurities will be visible. Atomic resolution electron energy loss spectroscopy is possible by locating the probe over particular atomic columns or planes seen in the image. This provides complementary information on low-Z species and chemical bonding. Such data represents an ideal starting point for first-principles theoretical calculations of energetics and dynamics, avoiding time-consuming searches of trial structures. Examples are shown of ordering in relaxer ferroelectrics, interfacial termination in oxide-oxide and metal-oxide interfaces, and an impurity-induced structural transformation of a ceramic grain boundary. Published by Elsevier Science Ltd.